2013
DOI: 10.1371/journal.pone.0070653
|View full text |Cite
|
Sign up to set email alerts
|

High Content Screening as High Quality Assay for Biological Evaluation of Photosensitizers In Vitro

Abstract: A novel single step assay approach to screen a library of photdynamic therapy (PDT) compounds was developed. Utilizing high content analysis (HCA) technologies several robust cellular parameters were identified, which can be used to determine the phototoxic effects of porphyrin compounds which have been developed as potential anticancer agents directed against esophageal carcinoma. To demonstrate the proof of principle of this approach a small detailed study on five porphyrin based compounds was performed util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(69 reference statements)
0
9
0
1
Order By: Relevance
“…The compounds were then subjected to a colorimetric MTS assay to assess their cytotoxicity. The compounds were tested over a range of concentrations with an illumination period of 2 min [ 37 ]. Unfortunately, none of the conjugates exhibited any phototoxic effect, which may be due to the relatively short illumination period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds were then subjected to a colorimetric MTS assay to assess their cytotoxicity. The compounds were tested over a range of concentrations with an illumination period of 2 min [ 37 ]. Unfortunately, none of the conjugates exhibited any phototoxic effect, which may be due to the relatively short illumination period.…”
Section: Resultsmentioning
confidence: 99%
“…Full details on the cell cultures and treatment, cell proliferation assay, high content imaging and analysis, statistical treatment, and illumination protocol are as given in Vaz et al . [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…To previously prepared 96-well assay plates containing cells in 100 μL of culture medium, test compounds, including mTHPC (Temoporfin®), at different concentrations (10-50 μM) and appropriate controls were added (untreated cells were used as control). After incubation for 24 h the medium was removed and changed for fresh one, dark controls were left in the dark for next 24 h. To assess the phototoxicity [26], the rest of the plates were illuminated for 2 min using Luxeon High Power LEDs (LXHL-BW03) as light sources emitting white light with a total fluence rate of 1.7 mW cm -2 and incubated for 24 h. 20 μL of the MTS dye solution was added to each well of the dark controls and illuminated plates and these were incubated for 3 h and the absorbance was recorded at 470 nm using a 96-well plate reader and imaging technique (InCell analyzer 1000 instrument, GE Healthcare).…”
Section: General Procedures For Cell Cultures and Cell Proliferation Amentioning
confidence: 99%
“…Preliminary investigations show that the water soluble P(V) porphyrin compounds, which are relatively easy to synthesize, can be used as versatile materials in PDT. Imaging analysis using high content screening (HCS) [26] showed that the P(V) porphyrins are readily taken up by SKGT-4 and OE33 cell lines after 24 h incubation and showed no visible toxicity in the dark. Images obtained by the InCell analyzer are shown in Figure 2 and show the photosensitizer uptake in red, dispersed within the cytoplasm of the cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Es identifiziert anhand eines Assays PDT‐Kandidaten spezifisch und nachgewiesen. Es bildet die Grundlage für automatisierte Screening‐Methoden 9…”
Section: Biomedizin: Porphyrine In Der Phototherapieunclassified